Pergaulan yang Bijak: Analisis Amsal 13:20 dan Aplikasinya terhadap Generasi Z - Vinny Elvira Walintukan; Ashar Mapule (Jurnal Ilmiah Tafsir Alkitab, 2024)
Social interaction is an unavoidable condition in social life. Scanning the social interactions of Generation Z in the current era, it is very free. Free social interaction means unlimited or uncontrolled interaction that can damage the morals of Generation Z. This research aims to discover Theological Principles in Proverbs 13:20 as advice for Generation Z in their daily interactions. This research method uses qualitative research methods with a literature study approach. The research results show that the theological principles in Proverbs 13:20 are: First, a wise person is one who processes with God. Second, a wise person is one who is consistent. Third, the role of community in social interaction. Fourth, choices and consequences. Fifth, the concept of foolishness. Proverbs 13:20 teaches the importance of choosing friends and social environments. Generation Z is expected to apply these principles of wisdom in their lives to achieve a meaningful life that aligns with God's will.